Fibrogenesis in Kidney Transplant: Dysfunction Progress Biomarkers - Costa, J S (2017)
Fibrogenesis markers, such as alpha-actin (AA), CD163 (macrophages), and E-cadherin, have been studied as chronic kidney allograft injury (CAI) predictors, a major cause of allograft failure. OBJECTIVE: Investigate the value of these markers in predicting CAI and initiation of dialysis. MATERIALS AND METHODS: Retrospective analysis of 26 kidney allograft biopsies (from 22 patients with CAI) during 2 years, evaluating intensity and percentage of marked cells on glomeruli and tubulointerstitial compartment. At the time of the biopsy, patients were 45.5 ± 15.8 years and 4.2 years after transplant, and they had a mean glomerular filtration rate (GFR) of 25.8 ± 9.9 mL/min. From an average of 8.5 glomeruli per biopsy, there was ≤25% sclerosis in 17 cases, 26% to 50% in 5, and >50% in 4. Interstitial fibrosis or tubular atrophy affected ≤25% of cortical area in 14 cases, 26% to 50% in 8, and >50% in 2. Twelve patients started dialysis 5.8 ± 4.7 years after transplant, with an average GFR 20.9 mL/min at the time of the biopsy. RESULTS: There was a higher intensity and percentage of CD163-marked cells in the tubulointerstitial compartment in advanced interstitial fibrosis. We found an association between intensity of AA in the tubulointerstitial compartment and initiation of dialysis (P = .003) and a negative correlation between intensity of E-cadherin loss and GFR (r = -0.56, P = .012). CONCLUSIONS: In our study, intensity of tubulointerstitial AA was shown to be a predictor of initiation of dialysis, and E-cadherin loss intensity was associated to CAI progression. However, prospective and larger studies are needed to evaluate the predictive value of these markers.